Ruby Bridges - Magoon, Kekla (She persisted (Philomel Books), 2021)
"As a first grader, Ruby Bridges was the first Black student to integrate William Frantz Elementary School in New Orleans, Louisiana. This was no easy task, especially for a six-year-old. Ruby's bravery and perseverance inspired children and adults alike to fight for equality and social justice." --